Case Report: Dual pathogenic mechanism of a PRKG2 missense variant underlies an attenuated phenotype of acromesomelic dysplasia - Akimova, Daria; Markova, Tatiana; Orlova, Maria; Kenis, Vladimir; Skoblov, Mikhail (Frontiers in Genetics, 2026)
Acromesomelic dysplasia comprises a group of rare skeletal disorders characterized by dwarfism with anomalies predominantly affecting the middle and distal segments of the limbs. Based on genetic variants, five types are recognized, with significant phenotypic variability even within a single type. Here, we describe a girl presenting with borderline short stature and mild disproportion due to acro- and mesomelic shortening of the limbs. Radiographic examination revealed shortening of the radius and ulna, mild brachydactyly, absence of iliac flaring and metaphyseal alterations of the long bones, and biconcave appearance of the femoral necks and II-IV metacarpals, and an elongated styloid process of the ulna. Using WGS, we identified two novel variants in the PRKG2 gene: a frameshift variant (NM_006259.3:c.1074del (p.Ala359LeufsTer24)) and a missense variant (NM_006259.3:c.1630G>T (p.Asp544Tyr)). Functional analysis unveiled a unique dual pathogenic mechanism: the missense variant creates a cryptic splice site, resulting in two aberrant protein products - an in-frame deletion and a missense substitution. We hypothesize that these alterations cause a partial, rather than a complete, loss of protein function, which may account for the patient’s attenuated clinical phenotype.